Trends, predictors and outcomes of need for hemodialysis after heart transplantation. (14th October 2021) - Briasoulis, A; Doulamis, I; Kampaktsis, P; Kuno, T; Alvarez, P
Abstract: Introduction: Acute renal failure is not uncommon immediately after heart transplantation (HT) and it is related to pre-existing cardiorenal syndrome, perioperative parameters, early post-operative course and initiation of calcineurin inhibitor therapy. We sought to investigate the trends, predictors and outcomes of renal failure requiring hemodialysis after HT. Methods: Adult HT recipients were identified in the United Network for Organ Sharing (UNOS) registry between 2009 and 2020. Patients were grouped according to the requirement for hemodialysis in the post-operative period after HT. Accounting for re-transplantation, Fine and Gray's test compared cumulative incidences of all-cause mortality between groups. Univariate and multivariate analysis were performed using the competing risk model. Results: A total of 26, 634 patients were included in the study including 3, 148 HT that required hemodialysis. Overall, the incidence of post HT dialysis increased during the study period (p<0.001, Figure 1). Patients on hemodialysis had significantly higher serum creatinine at the time of HT (1.51 vs. 1.21 mg/dl, p<0.001). Multivariable logistic regression analysis identified longer ischemic time (p<0.001), serum creatinine at HT higher than 1.2 mg/dl, higher calculated panel reactive antibody (%) (p=0.003), prior cardiac surgery (p<0.001), older donor age (p<0.001), higher recipient body mass index (p<0.001), mechanical ventilation at HT (p<0.001), support with extracorporeal membrane oxygenation (p<0.001) as independent predictors of hemodialysis need after HT. After adjusting for described confounders patients on hemodialysis had higher risk of 30-day (odds ratio 1.44, 95% CI 1.33–1.56, p<0.001) and all-cause mortality (sub-hazard ratio = 5.4, 95% CI 4.81–6.03, p<0.001) Conclusion: Over 1 in 10 HT recipients require hemodialysis after HT. Need for hemodialysis is associated with worse 30-day and long-term mortality after HT. Funding Acknowledgement: Type of funding sources: None.